Determination of Supply Strategy for Beef Price Stability in Balikpapan: Game Theory Approach - Bayu Nur Abdallah; Fatia Sukma Wardani; Christopher Davito Prabandewa Hertadi (Universitas Islam Raden Rahmat, Malang, 2024)
Fulfillment of beef availability needs to be considered to maintain a balance between supply and demand. This is because the market often experiences price fluctuations due to stock imbalances. This research aims to identify the most effective strategy using a game theory approach to guarantee the availability of beef and maintain price stability in Balikpapan, where Balikpapan always brings in beef from outside the area, both local and imported beef. This research provides valuable insight into the importance of collaboration between the parties involved, namely local beef traders and importers. This research also serves as a guide for decision makers in the beef industry to achieve an optimal balance between supply and demand. The results obtained through pure strategic analysis indicate a competitive situation between local traders and beef importers. Both parties adopted the same strategy to maintain a 100% stock level, which resulted value of the game is 55,673,262,189.